2018
DOI: 10.3390/brainsci8040056
|View full text |Cite
|
Sign up to set email alerts
|

Oxamate, but Not Selective Targeting of LDH-A, Inhibits Medulloblastoma Cell Glycolysis, Growth and Motility

Abstract: Medulloblastoma is the most common malignant paediatric brain tumour and current therapies often leave patients with severe neurological disabilities. Four major molecular groups of medulloblastoma have been identified (Wnt, Shh, Group 3 and Group 4), which include additional, recently defined subgroups with different prognosis and genetic characteristics. Lactate dehydrogenase A (LDHA) is a key enzyme in the aerobic glycolysis pathway, an abnormal metabolic pathway commonly observed in cancers, associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 37 publications
1
32
0
Order By: Relevance
“…In cancer cells, LDHA helps in rapid conversion of pyruvate to lactate, minimizing pyruvate entry into TCA cycle in the mitochondria. High levels of LDHA helps cancer cells to establish and proliferate by promoting epithelial to mesenchymal transition [31], angiogenesis [15], cytoskeletal remodeling [32], increasing cell motility [33], invasion and migration [34]. One advantage of LDH-5 upregulation for cancer cells is to maintain fuel supply under hypoxic conditions and expectedly a broad range of highly invasive hypoxic cancers show high LDH-5 levels.…”
Section: Ldha In Cancersmentioning
confidence: 99%
“…In cancer cells, LDHA helps in rapid conversion of pyruvate to lactate, minimizing pyruvate entry into TCA cycle in the mitochondria. High levels of LDHA helps cancer cells to establish and proliferate by promoting epithelial to mesenchymal transition [31], angiogenesis [15], cytoskeletal remodeling [32], increasing cell motility [33], invasion and migration [34]. One advantage of LDH-5 upregulation for cancer cells is to maintain fuel supply under hypoxic conditions and expectedly a broad range of highly invasive hypoxic cancers show high LDH-5 levels.…”
Section: Ldha In Cancersmentioning
confidence: 99%
“…Hence, altered expression of LDHC could be involved in maintaining an alternative energy source by contributing to the metabolic switch in cancer cells. In addition, increased LDHA and decreased LDHB expressions facilitate tumor formation and progression through remodeling of the tumor microenvironment, increasing proliferation, and inducing epithelial-to-mesenchymal transition, cell migration and invasion, and angiogenesis [10][11][12][13][14][15][16][17][18][19][20]. In line with this, two studies to date demonstrate that enhanced expression of LDHC induces epithelial-to-mesenchymal transition, matrix metalloproteinase-9 (MMP9) expression and promotes cancer cell migration and invasion [7,21].…”
Section: Introductionmentioning
confidence: 81%
“…The catalytic substrate of LDHA is competitively inhibited by oxamate, a pyruvate analog, and its effect has been identified in various cell lines (15,(37)(38)(39). A study by Zhao et al (15) demonstrated that oxamate inhibited the activity of gastric cancer cells in a dose-and time-dependent manner.…”
Section: Discussionmentioning
confidence: 99%